Twenty-Five Years of Educational Practice and Theory 1955–1979
VI, 358 p.
Keywords: In 1979 the International Rel'iel1' of Education celebrated its twenty-fifth anniversary. This book which now reproduces the two Jubilee issues of that Review has been published for a number of reasons. One is the importance of the topics dealt with. The last twenty-five years have seen unprecedented developments in education right across the world, in industrialised countries no less than in those which are still approaching that phase. From time to time it is essential to look back over the past and take stock of how the present situation has come about, to disentangle the trends and sort out from the welter of ideas those which turned out to be non-starters, those which died in their tracks, and those which came to stay. This is only possible after a certain passage of time has set events in proportion and in perspective. The twenty-five years which have elapsed since the IRE was started ten years after the ending of World War II would seem to be just long enough to make this possible, though when the IRE celebrates its fiftieth Jubilee in the year 2004 some of the trends which now seem so definite may themselves have died away to be replaced by others which can now be only dimly conceived. Another reason for this publication is the quality and standing in the world of education and scholarship of the two editors and their contributors.